Reflection on the importance of vaccination of people with cancer as a strategy in the prevention of complications of vaccine-preventable diseases - Moreira, Andrielly de Campos; Ferraz, Maria Isabel Raimondo (Seven Editora, 2023)
Reflective research, aimed to: Reflect on the importance of vaccinating people with cancer as a strategy in the prevention of complications of vaccine-preventable diseases. The basis for the reflections was based on national and international publications in the health area, related to the vaccination of people with cancer. Data collection was conducted between January 2022 and February 2023, in which publications from the health area were included. Thus, the reflection was elaborated in three chapters: Cancer: implications related to disease and treatment; Vaccination of people with cancer; Performance of nursing and other health professionals in the vaccination of people with cancer. As final considerations, it is necessary that, in addition to primary care services, oncology services must consider the insertion of protocols for immunization of cancer patients safely, to reduce the possibility of illness and complications due to diseases preventable by vaccination. DOI: https://doi.org/10.56238/alookdevelopv1-134